Myocardial Infarction without Obstructive Coronary Disease: Role of Images - Modesto dos Santos, Vitorino (2022)
This manuscript about myocardial infarction with nonobstructive coronary arteries (MINOCA) based on published studies aims to enhance the awareness of primary health workers about this potentially serious condition that often poses diagnostic challenges. Two Brazilian, one Chilean, and one Turkish studies are commented on, and the role of imaging evaluations to establish the diagnosis is emphasized